Competency in the era of teacher professional students - Rutsamejam, Kittiya; Tangchitcharoenkhul, Rungnapa; Pholpuntin, Sirote (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2023)
DOI:10.14456/pnuhuso.2023.17 The competency of teachers is vital for the development of education and the quality of learners; therefore, the educational institutes have set a framework of teachers’ competencies to develop and evaluate student teachers’ competencies as stated in the Thailand National Education Act, B.E. 2542 that the relevant organizations must supervise and cooperate with the educational institutions to prompt the development of student teachers’ competencies in the 21st century. Competency means hidden attributes of individuals as a result of knowledge, skills, motivations, attitudes, and other attributes that enable individuals to produce benchmark results in their responsible work. Thus, teachers’ competencies are essential for the effective practice of the teaching profession to meet the requirements of educational organizations in the education reform era. Also, Teachers Council of Thailand Board issued the announcement to define the details of competencies as the standard of knowledge and experience to practice the teaching profession. Thereby, it can be used as a criterion for accreditation of the degree or educational certificates for teaching profession which various institutions propose the Teachers Council to certify from the academic year 2019 onwards. Applicants for teachers’ licenses, both Thai and foreign teachers must pass the test and evaluation of teachers’ competencies. Therefore, teachers’ competencies are vital to develop qualities of teachers to be knowledgeable, competent, and to emphasis on the teaching-learning process along with the cultivation of morality, ethics and professional skills. Admittedly, the evaluation of all dimensions must involve teachers’ competencies to be in line with the changing era which emphasizes competencies as the basis for teaching and learning management and assessment, unlike focusing on the standard-based curriculum as before.